Fabrication and evaluation of a host-guest polylactic acid/gelatin-hydroxyapatite-blueberry scaffold for bone regeneration - Someyra Sistani; Samira Asgharzade; Samaneh Arab; Marjan Bahraminasab; Elahe Soltani-Fard (Journal of Orthopaedic Surgery and Research)
Abstract Bone tissue engineering aims to produce bone substitutes that are crucial for tissue repair. In this study, a three-dimensional (3D) host-guest scaffold model was developed. A porous polylactic acid (PLA) framework (host) was fabricated using a 3D printing technique to provide mechanical stability. The pores in the framework were subsequently occupied with nano-hydroxyapatite (HA), gelatin (G), and blueberry extract (BB) mixed with different ratios (guest). The physicochemical, mechanical, and biological behavior of the scaffolds were investigated. The results exhibited that all fabricated scaffolds degraded gradually as time progressed, with less than 20% degradation occurring within 56 days. The host-guest scaffolds favorably influenced the viability and attachment of MC3T3-E1 cells in vitro. Based on the MTT assay results, all scaffolds showed excellent cell viability, particularly HA10-BB40. Furthermore, the cell attachment increased on the surfaces of scaffolds with increasing HA and BB content. Specifically, high number of cells were observed on HA10-BB20 and HA10-BB40. Meanwhile, the best cell mineralization was detected in HA10-BB40 group. Additionally, the scratch assay also showed the ability of BB to enhance cell migration. According to these findings, HA10-BB40 was identified as the best scaffold composition and further analyzed for mechanical properties, wettability, apatite formation ability, and gene expression. The compressive strength of HA10-BB40 was 4.92 MPa, and its surface demonstrated hydrophilic characteristic. This scaffold formed a uniform apatite layer on its surface after 7 days of immersion in SBF. In addition, the expression of Runx2, Col1α1, and VEGF genes in HA10-BB40 significantly enhanced compared to the control group. This study showed the potential of the fabricated host-guest scaffolds, particularly HA10-BB40, as a favorable substrate for engineered bone replacements.